Mitos Dan Religi Dalam ‘Geguritan I Dukuh Siladri’ Karya Sastra Kreatif Dan Dinamis - A.A. Kade Sri Yudari; I Gusti Agung Paramita; I Gusti Ayu Ngurah (Jurnal Penelitian Agama Hindu, 2021)
This article is a small part of research report on the oral tradition of ‘Nyurud di Setra’ in the Klungkung-Bali Pakraman community Village Pemenang. One of the subsections reveals the relationship between myth and religion towards the traditional inherentance of Pura Dalem Suladri which is implicitly described in ‘geguritan I Dukuh Siladri’. With the qualitative interpretative descriptive methods, it is understood that religion is one elements of universal culture which containts of beliefs and behavior related to supernatural power and powers. Meanwhile, myth is an important part of human life as a psychological necessity due to woory and fear of the wrath universe. In order for humans to avoid disaster, sacred and sacred stories are about objects that govern the universe are built, strengthened by sacred buildings and religious rituals. Thus, the‘geguritan I Dukuh Siladri’ appears to be a creative and dynamic literary work following the reality cummunity of social life according to the time.